مشكلة السعادة في الفكر الإسلامي القديم الراغب الأصفهاني نموذجا: The Issue of al-saʿādaẗ in Classical Islamic Thought: Al-Raghib Al-Isfahani as a Model - امختاري, سعيد امختاري (الدراسات الإسلامية, 2025)
This study explores one of the most significant philosophical issues throughout history — the Issue of al-saʿādaẗ. Philosophers have approached this issue from diverse perspectives, and Islamic thought has contributed significantly to this discourse. This research focuses on the views of Al-Raghib Al-Isfahani as a representative of Muslim intellectual thought. The study begins by analyzing Al-Isfahani's definition of al-saʿādaẗ and his perspective on the means of attaining it, emphasizing that the pursuit of al-saʿādaẗ is a universal human endeavor. It then examines the limitations of human reason in understanding ultimate happiness, particularly in the afterlife. The research further discusses the possibility of achieving absolute saʿādaẗ within Islamic thought and the role of worldly al-saʿādaẗ in facilitating it. The study concludes by identifying the factors that undermine human saʿādaẗ. A combination of descriptive, analytical, and inductive methods has been employed to investigate the subject comprehensively.